Literature and Other Arts in Canada: Some Current Practices - MacDonald, Marylea (Romanica Silesiana)
Even a cursory examination of some current practices in literature and other arts in Canada reveals that we live in a time of cross-pollination between the arts. It is not an accident that we have reached this moment. The cultural shift has been brought about by the influence of pop culture, technology in the arts and media, and computers. The practices also translate a desire to collaborate, to pool creative energy, to break out of the mold of the solitary suffering artist. Art experienced as a collective creative process has different goals from individual artistic pursuits. Communication and exchange constitute a journey towards becoming whole. I will briefly discuss modes of inspiration that generate interaction, Margaret Atwood’s exemplary history of film and stage adaptation, with a focus on The Penelopiad, some other examples of collaboration between writers and other artists, and multi-disciplinary artists. Key words: Literature, inspiration, adaptation, collaboration, multi-disciplinary artists.